Bright Greenish Yellow Fluorescence and Aflatoxins - EJAZ, NUSRAT; SHEIKH, A. SALAM (Biological Sciences - PJSIR, 1997)
Contamination of oil seeds with aflatoxins may cause hazards to animals and human beings through contamination of poultry products and the milk of milch cattle. This study was undertaken to design a method to detect aflatoxin contamination by a simple and rapid test i.e. BGYF test or black light technique.